(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
This study aimed at investigating the ways in which university students face their psychological stress and its relation with study level. To achieve the goals of the study, the researchers built the psychological stress facing methods scale to suit Saudi environment after ensuring validity and reliability, Then, it was administrated to a sample of Qaseem university students (n=304). The results revealed that students used many strategies to face their Psychological stress: social support, problem solving, effective confrontation, religious support, avoid confrontation, and emotional confrontation. One Way ANOVA revealed that third and fourth years students were the most widely used methods of stress management, followed by second-year students, and finally first-year students. The results were discussed in light of previous studies, and some recommendations were suggested.